Determinantes socioeconômicos e ambientais do declínio das hospitalizações por diarréias em lactentes no Rio Grande do Norte - 1992 a 2001 - Andrade, Ion Garcia Mascarenhas de (2008)
There was a significant decline in hospitalizations for acute diarrhea in children younger than 1 year of age in Brazil between 1992 to 2001. The less economically developed state of Rio Grande do Norte is a case example of the national trend. In this work, we show a significant association between improvements in socioeconomic variables as well as increased access to sanitation and the decreased rate of hospitalization. Additionally, we observed a positive, seasonal correlation between rainfall and hospitalizations. Most notably, however, we show that improvements in income and inflation were positively correlated with a decline in hospitalizations. Improvements in public health infrastructure, socioeconomic variables like education and literacy, and increased investment in health services were important in reducing severe early childhood diarrheas. However, the data suggests that increased buying power and reductions in poverty played an equally crucial role in reducing hospitalizations for acute diarrhea in infants in Brazil. The work includes elements of the demography of the period for the age groups involved, children under one year, women in fertile age and fertility rate